PENGEMBANGAN BAHAN AJAR PERKEMBANGAN ANAK USIA SD SEBAGAI SARANA BELAJAR MANDIRI MAHASISWA - Kasina Ahmad; Ika Lestari (Perspektif Ilmu Pendidikan, 2010)
Instructional material is one of teh important learning resources in teaching and learning process. However, the course of The Development of Primary School Age Children at the Department of Primary School Teacher Education, School of Education, State University of Jakarta, has not a reference which can be used as a main text book. This research, therefore, developed a text book to meet the need. Applying research and development method introduce by Borg and Gal and tried out, this research has produce a main text book that has proved a high readability and signifiacnt to the course. It was also found out that the text book produce is able to motivate the students to learn and has improved the students’ learning achievement.